Pencil Graphite Electrodes: A Versatile Tool in Electroanalysis. (31st January 2017) - David, Iulia Gabriela; Popa, Dana-Elena; Buleandra, Mihaela
Abstract : Due to their electrochemical and economical characteristics, pencil graphite electrodes (PGEs) gained in recent years a large applicability to the analysis of various types of inorganic and organic compounds from very different matrices. The electrode material of this type of working electrodes is constituted by the well-known and easy commercially available graphite pencil leads. Thus, PGEs are cheap and user-friendly and can be employed as disposable electrodes avoiding the time-consuming step of solid electrodes surface cleaning between measurements. When compared to other working electrodes PGEs present lower background currents, higher sensitivity, good reproducibility, and an adjustable electroactive surface area, permitting the analysis of low concentrations and small sample volumes without any deposition/preconcentration step. Therefore, this paper presents a detailed overview of the PGEs characteristics, designs and applications of bare, and electrochemically pretreated and chemically modified PGEs along with the corresponding performance characteristics like linear range and detection limit. Techniques used for bare or modified PGEs surface characterization are also reviewed.